Merevitalisasi Penggunaan Bahasa Inggris pada Satuan Pendidikan - Yohanes Heri Pranoto; Anselmus Inharjanto (Ikatan Dosen Katolik Indonesia, 2020)
This study aims at revitalizing the role of the English language in education, where it becomes the house of the students for most time in their lives. When something wrong occurs and goes on the paradigm conformation of this revitalization, shifting assumption should become one of the efforts and be strived by one most element who takes main responsibility on education itself – teacher. This study explores empirically and theoritically the teachers’ paradigm on the use of English language in the real classroom. The participants were the teachers from private schools in Lahat and Bengkulu joining a workshop due to Hari Studi Guru conducted by the foundations. The workshop results were reflected and interpreted by the involvement of a related-literature review from previous researchers and experts - journal articles and scientific books.